Comparative study of two purified inulinases from thermophile Thielavia Terrestris NRRL 8126 and mesophile Aspergillus Foetidus NRRL 337 grown on Cichorium Intybus l - Fawzi, Eman Mohamed (Sociedade Brasileira de Microbiologia, 2011)
Thirty fungal species grown on Cichorium intybus L. root extract as a sole carbon source, were screened for the production of exo-inulinase activities. The thermophile Thielavia terrestris NRRL 8126 and mesophile Aspergillus foetidus NRRL 337 gave the highest production levels of inulinases I & II at 50 and 24 ºC respectively. Yeast extract and peptone were the best nitrogen sources for highest production of inulinases I & II at five and seven days of incubation respectively. The two inulinases I & II were purified to homogeneity by gel-filtration and ion-exchange chromatography with 66.0 and 42.0 fold of purification respectively. The optimum temperatures of purified inulinases I & II were 75 and 50 ºC respectively. Inulinase I was more thermostable than the other one. The optimum pH for activity was found to be 4.5 and 5.5 for inulinases I & II respectively. A comparatively lower Michaelis–Menten constant (2.15 mg/ml) and higher maximum initial velocity (115 µmol/min/mg of protein) for inulinase I on inulin demonstrated the exoinulinase’s greater affinity for inulin substrate. These findings are significant for its potential industrial application. The molecular mass of the inulinases I & II were estimated to be 72 & 78 kDa respectively by sodium dodecyl sulfate–polyacrylamide gel electrophoresis.